Clinical profile of vigabatrin as monotherapy for treatment of infantile spasms - Lerner, Jason T (Dove Medical Press, 2010)
Vigabatrin, the first therapeutic agent to be approved by the Food and Drug Administration for the treatment of infantile spasms, as well as for adjunctive use in the treatment of refractory complex partial epilepsy, represents an important advance for patients with difficult-to-manage epilepsy. This review summarizes the complex history, chemistry, and pharmacology, as well as the clinical data leading to the approval of vigabatrin for infantile spasms in the US. The long path to its approval reflects the visual system and white matter toxicity concerns with this agent. This review provides a brief description of these concerns, and the regulatory safety monitoring and mitigation systems that have been put in place to enhance benefit over risk.